2010
DOI: 10.2519/jospt.2010.3294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser Therapy (LLLT) in the Development of Exercise-Induced Skeletal Muscle Fatigue and Changes in Biochemical Markers Related to Postexercise Recovery

Abstract: investigating the effects of commonly used interventions, such as massage, lowintensity exercises, cryotherapy, hot-cold contrast baths, neuro-muscular electrical stimulation, and stretching, are few, and the results on effectiveness are mixed. 3 The rationale behind the use of these interventions is often related to mechanisms such as reducing postexercise inflammatory responses and the promotion of circulation and local metabolism t BacKgRound: Cell and animal studies have suggested that LLLT can reduce oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(87 citation statements)
references
References 36 publications
5
74
0
8
Order By: Relevance
“…Up to our knowledge, no previous literature showed the effect of conventional US or LLLT on the serum level of CRP in OA of the knee joint. One study reported decrease in post-exercise elevation of blood CRP as well as lactate and creatine kinase due to pre-exercise irradiation by low-level laser [31].According to the results of the current study, continuous US therapy was more effective in reduction of the inflammatory markers; IL-6, INF-gamma as well as elevation of the antiinflammatory cytokine IL-10 in the serum of Lev-induced OA of knee joint in rats.…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levosupporting
confidence: 49%
“…Up to our knowledge, no previous literature showed the effect of conventional US or LLLT on the serum level of CRP in OA of the knee joint. One study reported decrease in post-exercise elevation of blood CRP as well as lactate and creatine kinase due to pre-exercise irradiation by low-level laser [31].According to the results of the current study, continuous US therapy was more effective in reduction of the inflammatory markers; IL-6, INF-gamma as well as elevation of the antiinflammatory cytokine IL-10 in the serum of Lev-induced OA of knee joint in rats.…”
Section: Effects Of Ultrasound Versus Low Level Laser Therapy In Levosupporting
confidence: 49%
“…Lopes-Martins et al (2006) also observed a decrease in fatigue after application of LLLT in rat electrically-stimulated muscle. Leal et al (2008;2010b;2010c) reported that LLLT increased the number and duration of contractions in high intensity, short duration exercises designed for volleyball players. Although LLLT apparently increased the muscle fiber diameter at 3 h, this enhancement probably reflected the lower fiber diameter in control muscles rather than an increase caused by LLLT; this conclusion is supported by the fact that the diameter of LLLT-treated muscles at 3 h was similar to the diameters of control and LLLT-treated muscles at 9 h. The reason for the lower fiber diameter in the 3 h control group is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the LLLT is a widely used resource, it is in constant process of evaluating its various parameters and it needs more controlled studies to confirm their mechanisms of action in the various fields. The use of a single LLLT session has been used to assess their effects on endurance 16 , muscle performance, oxidative stress and fatigue 17 , however note that the use of only a therapeutic session is considered a limitation of this study, and that further studies could assess whether the sum therapies could significantly influence proprioception in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…When applied to stem cells it has been observed increased proliferation and cell differentiation 13 . In recent years, LLLT has been used aiming not only repair and analgesia, but to delay the levels of muscle fatigue 15 , reduce lactate levels, creatine kinase and C-reactive protein after exercise, and to increase muscle resistance 16 , increase muscle performance by delaying muscle fatigue 17 and increasing muscle torque 18 . Although biostimulants effects, there is a lack of research linking LLLT effects with proprioception, balance and movement control in healthy young women, since the research to date sticks in evaluating elderly 19 or with neurological disorders 20 and pain 21 ; so the aim of this study was to evaluate whether the application of infrared laser (830 nm) influence on proprioception in young women, given the potential both in sports and in athletes rehabilitation process.…”
Section: Introductionmentioning
confidence: 99%